2023
DOI: 10.3389/fgene.2022.1056114
|View full text |Cite
|
Sign up to set email alerts
|

Mesoangioblasts at 20: From the embryonic aorta to the patient bed

Abstract: In 2002 we published an article describing a population of vessel-associated progenitors that we termed mesoangioblasts (MABs). During the past decade evidence had accumulated that during muscle development and regeneration things may be more complex than a simple sequence of binary choices (e.g., dorsal vs. ventral somite). LacZ expressing fibroblasts could fuse with unlabelled myoblasts but not among themselves or with other cell types. Bone marrow derived, circulating progenitors were able to participate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 118 publications
0
2
0
Order By: Relevance
“…Given the complexities associated with achieving satisfactory integration into affected muscles, current research in cell-based therapies is focusing on harnessing secondary effects rather than primarily rescuing muscle integrity. For instance, engineered mesangioblasts hold promise to facilitate exon skipping without the necessity for repeated infusions [ 179 ].…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…Given the complexities associated with achieving satisfactory integration into affected muscles, current research in cell-based therapies is focusing on harnessing secondary effects rather than primarily rescuing muscle integrity. For instance, engineered mesangioblasts hold promise to facilitate exon skipping without the necessity for repeated infusions [ 179 ].…”
Section: Muscular Dystrophiesmentioning
confidence: 99%
“…During his invited lecture, giulio Cossu (University of Manchester, Uk and san raffaele Hospital, italy) demonstrated that mesoangioblasts, derived from adventitial pericytes of skeletal muscle, may be promising candidates for therapies of muscular dystrophies. recently, giulio's team has developed a new strategy that compensates for the low engraftment of transplanted mesoangioblasts in patients' muscles by genetically amplifying their dystrophin production (Cossu et al, 2023) and now works on immune-privileged mesoangioblasts as universal donor cells. The next speaker, radek sindelka (institute of Biotechnology, Czech academy of sciences, Czech republic), opened the floor for short, and thematically diverse, talks.…”
Section: Stem Cells and Regeneration -Developmental Biology Is Not Ju...mentioning
confidence: 99%